Modifying a naturalistic language intervention for use in an elementary school classroom. (January 2020) - Lane, Justin D; Shepley, Collin; Sartini, Emily; Hogue, Amanda
Background and aims: We evaluated a naturalistic language intervention (NLI) targeting expanded forms of expressive communication (e.g., two-word phrases) for elementary-aged children with autism spectrum disorder (ASD) and/or intellectual disability (ID). This study extends the findings of a previous study that evaluated an NLI for preschool-aged children who displayed social communication delays. In the previous study, one child was considered a non-responder to the original intervention; children with similar pre-intervention profiles to the non-responder were recruited for this study to evaluate a modified version of the NLI with a new participant group. Methods: The NLI was evaluated within the context of a multiple probe design across children, with sessions conducted in a public school classroom. The modifications to the NLI resulted in varying dosages of the intervention provided across sessions and children. To analyze the moderating influence of the variation in dosage, we graphed each dosage variable to allow for a formative analysis of changes within and across study conditions. Results: Results indicated increases in the target behavior for all three children when compared to probe sessions; however, for one child the consistency of changes were variable and, as such, may not be socially significant. Conclusions and implications: This study extends the literature on conducting NLIs with minimally verbal children with ASD and ID in dynamic settings, like classrooms. Educators and related professionals can capitalize on natural opportunities for social communication in children who are minimally verbal but imitative by using naturalistic procedures to promote verbalizations during age-appropriate activities.